2019
DOI: 10.3390/jof5010025
|View full text |Cite
|
Sign up to set email alerts
|

Mucormycosis in Burn Patients

Abstract: Patients with extensive burns are an important group at risk for cutaneous mucormycosis. This study aimed to perform a systematic review of all reported mucormycosis cases in burn patients from 1990 onward. A Medline search yielded identification of 7 case series, 3 outbreaks, and 25 individual cases reports. The prevalence reached 0.04%–0.6%. The median age was 42–48 in the case series and outbreaks, except for the studies from military centers (23.5–32.5) and in individual reports (29.5). The median total bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Mucormycosis of burn wounds has been known for more than one-half century to be associated with a high mortality and severe morbidity. Devauchelle et al recently reviewed the epidemiology of mucormycosis in burn patients [5]. They identified 7 case series, 3 outbreaks and 25 case reports containing infected patients.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mucormycosis of burn wounds has been known for more than one-half century to be associated with a high mortality and severe morbidity. Devauchelle et al recently reviewed the epidemiology of mucormycosis in burn patients [5]. They identified 7 case series, 3 outbreaks and 25 case reports containing infected patients.…”
Section: Epidemiologymentioning
confidence: 99%
“…Fungi of the order Mucorales are increasingly recognized as important causes of necrotizing wound infections in the setting of military (combat) injuries, burns, natural disaster-related, and other civilian trauma [1,2,3,4,5,6,7]. As the literature on these infections is widely distributed into journals across various disciplines, as well as lay press publications, we summarize herein the microbiology, pathogenesis, epidemiology, diagnosis, and treatment of wound-associated mucormycosis.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, local health structures unable to guarantee sterile irrigation of wounds and rapid care for patients with injuries may be another predisposing factor to post-traumatic mould infections during natural disasters [26,27]. Finally, patients with burn injuries are also at increased risk of developing post-traumatic mould infections [6,34,35]. Overall, the general picture stemming from these epidemiological data is that wound mould infections can be observed in previously healthy people who are affected by severe trauma [12,33,36].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…NA, not available. Comprehensive summaries of management of post-traumatic mould wound injuries in previous decades and in burn patients are available elsewhere [13,34] *Some cases of burn or postoperative mould wound infections were also included (4/16) **Cohort overlapping with that of other studies investigating different aspects of combat-related injuries [10,21,24,50,63] ***Possible cross-transmission…”
Section: Treatmentmentioning
confidence: 99%
“…The importance of cutaneous mucormycosis is highlighted in the paper of Devauchelle et al [12] who performed a systematic review of all cases of mucormycosis in burn patients reported in the international literature from 1990. The authors carefully described the prevalence, the epidemiological and clinical characteristics, as well as the diagnostic and therapeutic challenges of this clinical entity.…”
Section: Introductionmentioning
confidence: 99%